2014
DOI: 10.1021/ed400195c
|View full text |Cite
|
Sign up to set email alerts
|

Using Web-Based Video as an Assessment Tool for Student Performance in Organic Chemistry

Abstract: This article shows the potential for using video responses to specific questions as part of the assessment process in an organic chemistry class. These exercises have been used with a postbaccalaureate cohort of 40 students, learning in an online environment, over a period of four years. A second cohort of 25 second-year students taking the organic chemistry course onsite has been using these exercises over a period of three years. The questions in this exercise require the students to use a molecular model ki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 20 publications
(24 reference statements)
0
21
0
Order By: Relevance
“…1 There have been gradual changes to the methodology by which content has been delivered to the students, whereas only a small movement has been noted in the methods used for student assessment. 2 The general student body from grammar school to university demonstrates significant variation in amounts of exposure to and practice with new media and technology. Students are educationally, ethnically, and culturally diverse, leading to varying exposure to and experience with technology.…”
Section: Introductionmentioning
confidence: 99%
“…1 There have been gradual changes to the methodology by which content has been delivered to the students, whereas only a small movement has been noted in the methods used for student assessment. 2 The general student body from grammar school to university demonstrates significant variation in amounts of exposure to and practice with new media and technology. Students are educationally, ethnically, and culturally diverse, leading to varying exposure to and experience with technology.…”
Section: Introductionmentioning
confidence: 99%
“…1186). However, other studies illustrate how video can be used to capture cognitiveprocedural outcomes when students are tasked with documenting their completion of some experiment or exercise in the video rather than simply answering reflection questions (Erdmann & March, 2014;Speed, Lucarelli & Macaulay, 2018;Tierney, Bodek, Fredricks, Dudkin & Kistler, 2014). Speed et al (2018) asked biochemistry students to film video reports about experiments, with evidence of creative and critical thinking in videos and higher grades when compared with written lab reports.…”
Section: Discussionmentioning
confidence: 99%
“…Existing research has not informed the initiative and intentionality outcome; however, it would be helpful to know if the public video platform open to wider scrutiny encourages or discourages students from being honest and descriptive of their design process and from expressing vulnerability in describing any challenges or setbacks in design. Finally, with regard to the informal outcome engagement, a few studies have hinted that video assessment may be more engaging to students (Speed et al, 2018;Tierney et al, 2014). Speed et al (2018) reported that filming video reports was more engaging and enjoyable than writing reports.…”
Section: Q7mentioning
confidence: 99%
“…To improve the outcome for scenario #2, the students needed some motivation to look over the missed material on the exam. While there are some reports by others of alternative assessment strategies, including poster sessions (37)(38)(39), oral exams (36), and video responses (40), written examinations are still often the most practical form of assessment for chemistry courses.…”
Section: Collaborative Quizzes and Examsmentioning
confidence: 99%